Chapter Textgemeinschaften und die Erfindung von Rivalität und Toleranz in der Kaiserzeit (2./3. Jh. n. Chr.) - Rüpke, Jörg (De Gruyter, 2016)
1,700 years ago, the Roman emperors Constantine and Licinius granted religious freedom - even and particularly for Christianity. The religious policy of Constantine is often associated with the modern ideal of tolerance. This book inquires into the contours and shape of this modern concept as well as its meaning and scope in Late Antiquity. The history of research and reception of Constantine is also investigated.